PERANCANGAN SISTEM PENGAJUAN PERMOHONAN INFORMASI PUBLIK TERPADU BERBASIS WEB PADA PPID KEMENKOPUKM MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Pawit Wahib; Arya Tunggal Narotama; Nur Muhammad Rijki; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
This study aims to design a web-based integrated public information application submission system to Regional Information Management Officers of the Ministry of Cooperatives and Small and Medium Enterprises (PPID KemenKopUKM) using the Rapid Application Development (RAD) method. This system is designed to make it easier for the public to submit requests for public information online quickly and efficiently. The RAD method was used in the development of this system to minimize possible errors and allow for departmentalization and control. System development stages include requirements analysis, design workshop (modeling), construction, and implementation. Data collection methods used are observation, interviews, and literature study. Analysis of the current system at the KemenKopUKM PPID shows that submitting public information is done manually by visiting the office and filling out forms, which impedes the information service process. The proposed system uses information technology in the form of a website with two levels of access rights for applicants and admins. System design includes use case diagrams, activity diagrams, sequence diagrams, and database design using entity relationship diagrams (ERD) and logical record structure (LRS). It is hoped that the system designed will facilitate the KemenKopUKM PPID in serving the community more accurately, quickly and efficiently.